Forbidden Films : The Filmmaker & Human Rights. (Toronto : Toronto Arts Group for Human Rights, 1984)
Burton, Julianne ; Gumucio Dagron, Alfonso ; de Antonio, Emile ; Hayeem, Ben ; Mallet, Marilu ; Nemec, Jan ; Pick, Zuzana ; Rojas, Leuten
Forbidden Films : The Filmmaker & Human Rights, In Aid of Amnesty International, Toronto, October 18 - 28, 1984
English
kunstcatalogus